UJI VALIDITAS BOOKLET MARS: MANAJEMEN AKTIF REDUKSI STRES PADA GURU PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS - MUFLIHA, IZZAH; Rahman, Marlita Andhika; Andriani , Annisa (Jurusan Pendidikan Luar Biasa, 2025)
Special educator experience high levels of stress. However, this is not balanced with effective stress management skills, as they tend to rely primarily on emotion-focused coping strategies. Furthermore, there is no existing intervention guide that teaches the application of stress management strategies centered on problem solving. The MARS booklet was developed as a psychoeducational medium and guide based on the cognitive appraisal process approach, emphasizing problem-focused coping through the strategies of planful problem solving and seeking social support. This study aims to examine the content validity of the MARS Booklet as a psychoeducational medium and guide for special educators in managing stress. The study employed a Research and Development method, consisting of stages problem identification, data collection, product design, validation test, and product revision. The booklet was evaluated by four validators comprising a clinical psychologist, an educational psychologist, and special educators from public and private schools. Data were analyzed using Aiken's V formula and descriptive analysis. The MARS Booklet obtained overall content validity scores ranging from 0.75 to 1.00, categorized as high to very high. Validators provided suggestions and feedback regarding adjustments to content, language, and overall design, as well as the inclusion of a user guide for special educators. The MARS Booklet has been declared content valid as a psychoeducational medium and guide for stress management among special educators.